Overmodulation and field weakening in direct torque control of induction motor drives - Ahmad, M. Z.; Nik Idris, Nik Rumzi (2006)
During transient states, for instance during acceleration and deceleration, the inverter used in an induction motor drive normally operates in overmodulation in order to efficiently utilize the DC-link voltage. Beyond the based-speed, the flux is normally reduced proportionally with speed to extend the speed range of the drive system. The capability of the induction motor drive under overmodulation and field weakening modes are important, especially in electric vehicle applications, where the available power is limited and the speed range needs to be increased to avoid the use of the mechanical gears. This paper presents the performance of the direct torque control (DTC) of an induction motor drive under the overmodulation and field weakening conditions for constant frequency torque controller-based DTC drive. The results obtained showed that the drive system is capable of operating in Overmodulation and field weakening regions without resolving to the common approach of space vector modulation (SVM) based approach.